Useful Brazilian plants listed in the manuscripts and publications of the Scottish medic and naturalist George Gardner (1812–1849). (23rd February 2015) - Fagg, Christopher W.; Lughadha, Eimear Nic; Milliken, William; Nicholas Hind, D.J.; Brandão, Maria G.L.
Abstract: Ethnopharmacological relevance: Information regarding the beneficial use of native Brazilian plants was compiled by a number of European naturalists in the 19th century. The Scottish surgeon botanist George Gardner (1812–1849) was one such naturalist; however, the useful plants recorded in his manuscripts have not yet been studied in depth. Aim of the study: To present data recorded by Gardner in his manuscript Catalogue of Brazilian Plants regarding the use of native plants by Brazilian people and evaluate the extent to which they have been explored. Materials and methods: Data on useful plants were obtained from Gardner׳s manuscript Catalogue of Brazilian Plants deposited in the Archives of the Royal Botanic Gardens, Kew, UK. The identification of each plant was determined and/or updated by consulting the preserved botanical collections of Gardner deposited in the Herbarium of the Royal Botanic Gardens, Kew (hereafter K), and expert determinations in other herbaria where duplicates are held. Correlated pharmacological studies for each plant were obtained from the PubMed database. Information recorded in Gardner׳s diary and previously published elsewhere complemented these data. Results: A total of 63 useful plants was recorded from the Catalogue and a further 30 from Gardner׳s book Travels in the Interior of Brazil (Gardner, 1846 ). Of the recorded names in the Catalogue, 46 (73%) could be identified to species by consulting specimens collected by Gardner and held at Kew. Thirty-six different traditional uses were registered for the identified plants, the most common being as febrifuges, to treat venereal complaints and as purgatives. Fewer than 50% of these species have been the focus of published pharmacological studies, yet for those which have been thus investigated, the efficacies reported by Gardner were confirmed. Conclusion: The data recorded by Gardner represent a rich, relatively unexplored source of information regarding the traditional uses of Brazilian plants which merits further investigation. Graphical abstract: